2009
DOI: 10.1038/ismej.2009.121
|View full text |Cite
|
Sign up to set email alerts
|

Conversion and conservation of light energy in a photosynthetic microbial mat ecosystem

Abstract: Here we present, to the best of our knowledge, the first balanced light energy budget for a benthic microbial mat ecosystem, and show how the budget and the spatial distribution of the local photosynthetic efficiencies within the euphotic zone depend on the absorbed irradiance (J abs ). Our approach uses microscale measurements of the rates of heat dissipation, gross photosynthesis and light absorption in the system, and a model describing light propagation and conversion in a scattering-absorbing medium. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 43 publications
4
61
2
Order By: Relevance
“…Similarly, the heat budgets of intertidal invertebrates during air exposure sensibly ignore metabolic heat production, which is all but negligible when compared to irradiance, convection, and conduction (Helmuth 1998). Energy budgets in optically dense microbial mats also showed that heat dissipation from light absorption is predominant (Al-Najjar et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the heat budgets of intertidal invertebrates during air exposure sensibly ignore metabolic heat production, which is all but negligible when compared to irradiance, convection, and conduction (Helmuth 1998). Energy budgets in optically dense microbial mats also showed that heat dissipation from light absorption is predominant (Al-Najjar et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Fluxes of incident light energy were estimated from the measured downwelling irradiance, assuming that the average energy content of photons of photosynthetically available radiation is 217.5 kJ (mol photons) − 1 (Al-Najjar et al, 2010). The fraction of the incident light energy absorbed by the cyanobacterial population in the mats was estimated from the measured reflectance of the mats (see Supplementary Information 1).…”
Section: Microsensor Measurements Under Controlled Light Conditionsmentioning
confidence: 99%
“…About 3.8ˆ10 24 J solar energy is annually absorbed by the surface and atmosphere of the Earth, 95.5% of which dissipates as the sensible and latent heat fluxes, only 4.5% is channeled into photosynthesis [6,7]. The photosynthesis using the photosynthetically active radiation (PAR) as the energy source is the only process by which carbon dioxide (CO 2 ) is converted into organic carbon and the solar energy is converted into chemical energy and stored as biomass [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…About 3.8ˆ10 24 J solar energy is annually absorbed by the surface and atmosphere of the Earth, 95.5% of which dissipates as the sensible and latent heat fluxes, only 4.5% is channeled into photosynthesis [6,7]. The photosynthesis using the photosynthetically active radiation (PAR) as the energy source is the only process by which carbon dioxide (CO 2 ) is converted into organic carbon and the solar energy is converted into chemical energy and stored as biomass [6,8]. Once stored, the biomass can provide food for heterotrophic organisms and can be processed into usable energy such as renewable fuel or bioenergy, which has currently attracted great interest in the global energy scenario [6,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation